KEMAMPUAN MENGHITUNG BESAR ARUS DAN BESAR TEGANGAN PADA RANGKAIAN LISTRIK ARUS SEARAH SISWA KELAS X JURUSAN ELEKTRONIKA INDUSTRI SMK NEGERI 2 PEKANBARU - Ronny Yusanti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This study aims to determine and explain the level of ability to answer the problems according to the procedureof solving the problem of class X students Elementary Electronics Elementary SMK Negeri 2 Pekanbaru evensemester of the academic year 2017/2018. The research method is descriptive research. The research was doneby using problem solving test for four questions. Data source 30 students. The results showed that the level ofability of students of class X Basic Electronics Elementary SMK Negeri 2 Pekanbaru in answering the problemsolving problem is in the range 70.00 - 84.99. Thus, the problem solving skills of students of class X BasicElectronics Elementary SMK Negeri 2 Pekanbaru categorized good.